2020
DOI: 10.1177/2333721420985975
|View full text |Cite
|
Sign up to set email alerts
|

A Question of Access: Exploring the Perceived Benefits and Barriers of Intelligent Voice Assistants for Improving Access to Consumer Health Resources Among Low-Income Older Adults

Abstract: Intelligent voice assistants (IVAs) such as Amazon Echo and Google Home present a promising opportunity to improve access to consumer health information and resources for older adults. However, researchers know little about older adults’ opinions of using IVAs for these potentially critical tasks, particularly those with already limited access. In this paper, we explore older adults’ views about IVAs for consumer health and wellness information with the goal of better understanding what they envision as benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 45 publications
2
62
0
Order By: Relevance
“…Following the recent Dr Google phenomenon [3], conversational agents have quickly become a source of knowledge for health-related requests, providing information on various physical and mental health conditions [4]. Over the past years, advances in machine learning, particularly in neural networks, have enabled voice-based technologies to assist health professionals during medical consultation [5], provide diagnostic support [6], assist elderly people in their daily routines [7,8], and promote an overall healthier lifestyle [9]. Furthermore, intelligent assistants show potential in recognizing emotions and developing robot-human relationships with users [10,11], which can open a wide range of new applications for mental health patients, after-diagnosis support, and treatment of chronic conditions [12].…”
Section: Overviewmentioning
confidence: 99%
“…Following the recent Dr Google phenomenon [3], conversational agents have quickly become a source of knowledge for health-related requests, providing information on various physical and mental health conditions [4]. Over the past years, advances in machine learning, particularly in neural networks, have enabled voice-based technologies to assist health professionals during medical consultation [5], provide diagnostic support [6], assist elderly people in their daily routines [7,8], and promote an overall healthier lifestyle [9]. Furthermore, intelligent assistants show potential in recognizing emotions and developing robot-human relationships with users [10,11], which can open a wide range of new applications for mental health patients, after-diagnosis support, and treatment of chronic conditions [12].…”
Section: Overviewmentioning
confidence: 99%
“…Third, a benefit has been identified in the health domain. VAs can assist with daily well-being activities such as health tracking, medication management, or dietary planning (Tsiourti et al, 2014;Nallam et al, 2020;Trajkova and Martin-Hammond, 2020). Fourth, the use of VAs might contribute to enjoyable leisure time experiences, via entertainment features like music, videos, and jokes (Scherr et al, 2020;Corbett et al, 2021).…”
Section: Benefits Of Voice Assistantsmentioning
confidence: 99%
“…In this way, the benefit of support for independent living and a reduction of dependency on personal assistance may also result in a higher level of dependency on VA assistance. Finally, concerns about privacy and data security are potential barriers to using VAs (Nallam et al, 2020;Trajkova and Martin-Hammond, 2020).…”
Section: Challenges Of Voice Assistants and Limitations In Current Research On Voice Assistants In Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two papers in this collection focussing on voice assistants or smart speaker technology. The fifth paper in this special issue is by Nallam et al (2020) who explored using voice assistants or smart speakers to provide health information to older adults from low-income backgrounds. However, the sixth paper by Chung et al (2021) identified low-income older people living in residential accommodation using smart speakers or VA technology to provide reminders and support for their daily needs, such as a daily living assistance tool, a social activities reminder, a medical appointment reminder, a medication reminder and an information provider including providing health tips and the news.…”
Section: Introducing the Papersmentioning
confidence: 99%